2014
DOI: 10.1086/678066
|View full text |Cite
|
Sign up to set email alerts
|

Economic Impact of Redundant Antimicrobial Therapy in US Hospitals

Abstract: Our study suggests that there may be pervasive use of redundant antimicrobial therapy within US hospitals. Appropriate use of antimicrobials may reduce the risk of harm to patients and lower healthcare costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 32 publications
2
35
0
1
Order By: Relevance
“…Unnecessary antibiotic use contributes to the selection of multidrug resistant organisms, 27 wastes healthcare resources, 28 and likely leads to a significant number of adverse patient events annually. 29, 30 Thornhill et al identified that even short antibiotic treatment durations associated with endocarditis prophylaxis are associated with adverse reactions, including Clostridium difficile .…”
Section: Discussionmentioning
confidence: 99%
“…Unnecessary antibiotic use contributes to the selection of multidrug resistant organisms, 27 wastes healthcare resources, 28 and likely leads to a significant number of adverse patient events annually. 29, 30 Thornhill et al identified that even short antibiotic treatment durations associated with endocarditis prophylaxis are associated with adverse reactions, including Clostridium difficile .…”
Section: Discussionmentioning
confidence: 99%
“…Inappropriate antimicrobial agent use can lead to negative clinical outcomes including increased adverse drug events, Clostridioides difficile infection, antimicrobial resistance, and mortality . Although the total cost of inappropriately treated infections is unknown, redundant antibiotic use alone accounts for at least $12 million annually for United States hospitals . Involvement of clinical pharmacists in the care of infected critically ill patients' care can reduce these expenditures and improve clinical outcomes .…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Although the total cost of inappropriately treated infections is unknown, redundant antibiotic use alone accounts for at least $12 million annually for United States hospitals. 9 Involvement of clinical pharmacists in the care of infected critically ill patients' care can reduce these expenditures and improve clinical outcomes. 10 However, the burden of recognizing and resolving inappropriate antimicrobial use is not incumbent on any specific individual; rather, all health care team members must participate in antimicrobial stewardship (AMS) efforts.…”
mentioning
confidence: 99%
“…Such infections result in considerable morbidity, mortality, and crosstransmission in and between healthcare settings, as well as significant economic cost. 7 Antibiotic exposure is the single most important risk factor for the development of Clostridium difficile, a spore-forming bacillus that causes pseudomembranous colitis, manifesting as diarrhea that for some patients can progress to sepsis and death. 5 In fact, antibiotics are prescribed, often incorrectly, for the majority of patients hospitalized in US acute care hospitals.…”
Section: Introductionmentioning
confidence: 99%